Effects of Long‐Term Desiccation on Zooplankton Resting Egg Banks From Tropical Lake Sediments - Portinho, Jorge Laço [UNESP]; Perbiche‐Neves, Gilmar (Wiley, 2025)
ABSTRACT Dormant egg banks may be vulnerable to climate change and extreme events, such as prolonged droughts in lakes. However, there is currently no information on this issue regarding Neotropical zooplankton. This study aimed to evaluate the viability of dormant zooplankton eggs and to investigate their hatching success following an extended period of desiccation (7 years). Natural lake sediments with dormant egg banks were subjected to experimental desiccation for periods of 2 and 5 months, and 1, 6, and 7 years. After each desiccation period, we conducted ex situ hatching experiments to compare the structure (abundance and taxon richness) and composition of emerging zooplankton communities. Long‐term desiccation (6 and 7 years) led to a loss of zooplankton taxa, and the effects of desiccation differed between the resting stages of microcrustaceans and rotifers. Microcrustacean hatching was unaffected up to 1 year of desiccation but was null after 6 years. In contrast, desiccation‐tolerant rotifer stages (e.g., Lecane elsa and Bdelloidea) persisted through 6 or 7 years of desiccation and hatched upon rehydration. Results showed distinct species compositions among the experimental desiccation periods. Periods of prolonged desiccation periods reduced the taxonomic richness and abundance of zooplankton hatching from sediments, leading to subsequent changes in the structure and composition of the zooplankton assemblage wich differed among different durations of experimental desiccation. Our findings show that long‐term droughts in lakes, intensified by changes in climate, may alter freshwater zooplankton communities. By demonstrating the resilience of rotifers and the vulnerability of microcrustaceans to prolonged desiccation, this study shows that different components of zooplankton communities will respond differently to future climates.